Pelaksanaan Program Ekstrakurikuler Tahfidz Al-Qur’an di MTs Negeri 1 Palembang - Amilda, Amilda; Atika, Nyimas; Zainap, Siti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the implementation of the Tahfidz Al-Qur'an extracurricular program at MTs Negeri 1 Palembang as an effort to develop students' character based on Islamic values. This research employs a qualitative method with a phenomenological approach. The subjects of the study consist of 12 individuals, including the vice principal in charge of student affairs, the head of the tahfidz program, teachers, and students participating in the Tahfidz Al-Qur'an program. Data collection methods used include observation, interviews, and documentation. Data analysis employs a phenomenological approach by examining phenomena or events occurring in the surrounding environment and life. The process involves three steps: collecting data on the implementation of the Tahfidz Al-Qur'an extracurricular program, reducing or categorizing data, presenting data, and drawing conclusions, followed by validating the data. The findings reveal that the implementation of the Tahfidz Al-Qur'an extracurricular program at MTs Negeri 1 Palembang takes place after school activities, focusing on memorization and revision (murojaah). The memorization methods used align with those established at MTs Negeri 1 Palembang and are adjusted to the methods preferred by teachers and students while ensuring recitations adhere to tajweed rules.